The relationship between knowledge and attitudes of pregnant women about pregnancy exercises with the smooth process of normal labor - Maulina Mawaddah; Eka Sylvian Siregar (Science Midwifery, 2023)
During pregnancy a mother will experience various changes - both anatomical and physiological changes. Pregnant gymnastics is one of the activities in services during pregnancy or prenatal care which aims to prepare and train the muscles so that they can be optimally utilized in normal childbirth. The purpose of this study was to identify the relationship between knowledge and attitudes of pregnant women with the implementation of pregnancy exercises. This type of research is quantitative analytic using cross sectional design. Sampling technique with purposive sampling through non probability sampling as many as 55 people. The results showed that most pregnant women had good knowledge about pregnant gymnastics, as many as 40 respondents (72.7%), had a positive attitude towards pregnant gymnastics, as many as 36 respondents (65.5%), and 32 respondents (58.2%) did not do pregnant gymnastics Based on bivariate data analysis, obtained p value = 0.037, which means there is a relationship between knowledge and the implementation of pregnant gymnastics (p < 0.05). Significant results were also obtained p value = 0.001, which means there is a relationship between attitude with the implementation of pregnant gymnastics (p < 0.05). Based on the results of this study, the authors suggest increasing health promotion about pregnant gymnastics, and holding a pregnant gymnastics program for pregnant women.